(3GdcGajIs - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3hgj cSQ GdgGA Ch SchfgG GNJda ajgG abjd EfgG ddYWa hGdLGeY Hjf GdeYWhajf GdHjGf CYfj GdJYQja dHjGf eaghes
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3Ch Ydi KGfjgG CYfj GdaJMI hGdefUhH CYfj LQG Yde Chd GdefUhHjf CYfj QaYG Ch Ydi KGfjgG CYfj fUHGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs